An Investigation of Commitment in Auto-Repairs Service - Jayaram, Ram (2005)
This thesis examines the extent to which commitment helps us explain the relationship between service quality and a number of relational behavioral intentions (repurchase,advocacy, willingness to pay more, switching, neglect, private response, internal response and third-party response). The thesis identifies three components of commitment; an affective component, a continuance component based on sacrifice and a continuance component based on lack of choice. These components of commitment were hypothesized as mediators of the relationship between service quality and behavioral intentions. The proposed model has been tested in the auto-repair services. In general, the thesis provides support for the hypothesis that the components of commitment serve as mediators of the relationship between service quality and behavioral intentions which may be broadly construed as "loyalty" related (repurchase,advocacy and willingness to pay more). There is less support for hypotheses about the other dependent variables. This thesis makes a contribution to the relationship marketing literature because it has provided evidence that commitment is marketing relationships contains multiple components. This study also makes a contribution to the service quality literature because it provides evidence that the relationship between service quality and its behavioral consequences depends on the component of commitment that is brought forward in marketing relationships.